Analysis of Clinical and Genetic Characterization of Three Ataxia-Telangiectasia Pedigrees With Novel ATM Gene Mutations - Peng Huang; Peng Huang; Lu Zhang; Lu Zhang; Li Tang; Li Tang; Yi Ren; Yi Ren; Hong Peng; Hong Peng; Jie Xiong; Jie Xiong; et al. (Frontiers Media S.A., 2022)
ObjectiveThe clinical manifestations of ataxia-telangiectasia (AT) are very complex and are easily misdiagnosed and missed. The purpose of this study was to explore the clinical characteristics and genetic features of five pediatric patients with AT from three pedigrees in china.MethodsRetrospectively collected and analyzed the clinical data and genetic testing results of five AT patients diagnosed by the Whole-exome sequencing followed by Sanger sequencing. The five patients with AT were from three pedigrees, including two female patients (case 1 and case 2) in pedigree I, one male patient (case 3) in pedigree II, and two male patients (case 4 and case 5) in pedigree III. According to the United Kingdom Association for Clinical Genomic Science Best Practice Guidelines for Variants Classification in Rare Disease 2020 to grade the genetic variants.ResultsFive patients had mainly clinical presentations including unsteady gait, dysarthria, bulbar conjunctive telangiectasia, cerebellar atrophy, intellectual disability, stunted growth, increase of alpha-fetoprotein in serum, lymphopenia. Notably, one patient with classical AT presented dystonia as the first symptom. One patient had recurrent infections, five patients had serum Immunoglobulin (Ig) A deficiency, and two patients had IgG deficiency. In three pedigrees, we observed five pathogenic variants of the ATM gene, which were c.1339C>T (p.Arg447Ter), c.7141_7151delAATGGAAAAAT (p.Asn2381GlufsTer18), c.437_440delTCAA (p.Leu146GlnfsTer6), c.2482A>T (p.Lys828Ter), and c.5495_5496+2delAAGT (p.Glu1832GlyfsTer4). Moreover, the c.437_440delTCAA, c.2482A>T, and c.5495_5496+2delAAGT were previously unreported variants.ConclusionsPediatric patients with classical AT may present dystonia as the main manifestation, or even a first symptom, besides typical cerebellar ataxia, bulbar conjunctive telangiectasia, etc. Crucially, we also found three novel pathogenic ATM gene variants (c.437_440delTCAA, c.2482A>T, and c.5495_5496+2delAAGT), expanding the ATM pathogenic gene mutation spectrum.